Shadow kingdom [compact disc] - Dylan, Bob, 1941- (Columbia/Legacy, 2023)
Shadow Kingdom presents Dylan performing revelatory 21st century versions of songs from his storied back catalog ? including fan favorites like "Forever Young" and "It?s All Over Now, Baby Blue," and deep catalog gems like "Queen Jane Approximately" and "Wicked Messenger." Originally reinterpreted for an exclusive streaming film event, which aired in July 2021, Shadow Kingdom will now be available on vinyl, CD, and streaming platforms for the first time. The album's setlist includes 13 original songs handpicked by Dylan for his Shadow Kingdom performance plus the closing instrumental, "Sierra's Theme."